2010
DOI: 10.1152/ajpregu.00550.2009
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Akt/mammalian target of rapamycin pathway in skeletal muscle is associated with increased REDD1 expression in response to chronic hypoxia

Abstract: Although it is well established that chronic hypoxia leads to an inexorable loss of skeletal muscle mass in healthy subjects, the underlying molecular mechanisms involved in this process are currently unknown. Skeletal muscle atrophy is also an important systemic consequence of chronic obstructive pulmonary disease (COPD), but the role of hypoxemia in this regulation is still debated. Our general aim was to determine the molecular mechanisms involved in the regulation of skeletal muscle mass after exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
119
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 41 publications
14
119
3
2
Order By: Relevance
“…In addition, at the molecular level this effect is associated with a significant induction of the MAFbx, suggesting an activation of proteasomal degradation which could contribute to a reduction in skeletal muscle mass (Gomes et al, 2001). Thus these data are in agreement with previous studies suggesting a direct effect of hypoxia per se in the induction of skeletal muscle atrophy independent of energy intake status (Bigard et al, 1996;Favier et al, 2010;Pison et al, 1998). Interestingly, comparison between H vs Npf groups showed a significant decrease in muscle weight in the SOL but not the GAS muscle (Table 1).…”
Section: Version Postprintsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, at the molecular level this effect is associated with a significant induction of the MAFbx, suggesting an activation of proteasomal degradation which could contribute to a reduction in skeletal muscle mass (Gomes et al, 2001). Thus these data are in agreement with previous studies suggesting a direct effect of hypoxia per se in the induction of skeletal muscle atrophy independent of energy intake status (Bigard et al, 1996;Favier et al, 2010;Pison et al, 1998). Interestingly, comparison between H vs Npf groups showed a significant decrease in muscle weight in the SOL but not the GAS muscle (Table 1).…”
Section: Version Postprintsupporting
confidence: 93%
“…We further demonstrated that CoCl 2 requires the presence down-regulated in rat skeletal muscle in response to chronic hypoxia indicating that hypoxia negatively regulates protein synthesis in skeletal muscle (Favier et al, 2010). Therefore, the parallel actions of myostatin and hypoxia on protein synthesis suggest that induction of myostatin by hypoxia could represent a potential mechanism for hypoxia-induced atrophy.…”
Section: Version Postprintmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous research has demonstrated that chronic exposure to hypoxia adversely affects protein kinase B/mTOR signalling [123], up-regulates myostatin expression [124], and subsequently leads to atrophy in skeletal muscle [125].…”
Section: Intramuscular Signalling Pathwaysmentioning
confidence: 99%
“…Muscle atrophy has already been observed in humans after expeditions in high altitude (44), while a reduction in muscle growth has been shown in rodents chronically exposed to hypobaric hypoxia (7,16). In vitro studies showed that the Akt/mTOR pathway could be inhibited by hypoxia exposure (12,27,31), but to our knowledge, only few in vivo studies reported that prolonged hypoxia exposure altered this signaling pathway in skeletal muscles (16). Myostatin, a mediator of muscle atrophy, has been shown to partly account for the hypoxia-induced effects on muscle mass (20).…”
mentioning
confidence: 99%